Application of Cooperative Learning Model Think-Talk-Write Type for Improving Intensive Reading Skills - Nurmalina Nurmalina (Universitas Pahlawan Tuanku Tambusai, 2020)
The low level of intensive reading skill in Indonesian language of fourth grade of MI Darussalam becomes the background of this classroom action research. The ineffectiveness of the learning process is suspected by the lack of innovation and creativity of teachers in choosing a learning model. Therefore, the researcher applies cooperative learning model of Think-Talk-Write type as an effort to improve intensive reading skill of the fourth grade of MI Darussalam. Researcher is as the research subject and the fourth grade teacher of MI Darussalam is as observer. Data collection techniques conducted in this study are by using the techniques of observation, tests, and documentation. After conducting the research, it can be concluded that the average score of students' intensive reading skill before the research was 55,85 with less category. In the first cycle there has been an increase to 69.75 with sufficient category. Big changes occurred in cycle II with average value to 88.75 with good category. From the result of the research, it can be concluded that intensive reading skill of fourth grade of MI Darussalam can be increased by applying cooperative learning model type Think-Talk-Write.